Analysis of short-term temporal variations of 222Rn, other naturally occurring radionuclides, stable elements and environmental parameters in groundwater and surface drinking water in Norway - Aarsand, Aleksander Sverdrup; Mrdakovic Popic, Jelena; Teien, Hans-Christian (Frontiers in Public Health, 2025)
IntroductionExposure to radon-222 (222Rn) is a common problem in areas with high uranium-238 (238U) content in the subsurface. The gas may enter dwellings through cracks and gaps in the foundation, or groundwater collected for household use. It is well documented that 222Rn poses a health risk, especially in high concentrations. In water, the gas often co-occurs with other naturally occurring radionuclides (NOR), such as radium-226 (226Ra) and polonium-210 (210Po). These may, in combination with chemically toxic elements, negatively affect water quality and consequently human health.Materials and methodsTo investigate 222Rn content in drinking water and changes over time, water quality in six sampling points in western Norway were monitored over a period of 17 months. The majority of NORs, stable elements and general water parameters were found to be within accepted limits for drinking water quality in Norway. However, one of the sampling points, a drilled granite well, displayed high activity concentrations of 222Rn (up to 1,225 Bq/L), 210Pb (up to 41.7 mBq/L) and 210Po (up to 312 mBq/L). Water from other sampling points displayed low pH (5.8–6.5), which could affect mobility and bioavailability of toxic elements.DiscussionThe magnitude of variation of 222Rn activity concentration was generally reflected in other parameters, such as Ca and 238U, but statistically significant correlation (p < 0.05) could only be found in three sampling points. Several water parameters, such as Ca, electrical conductivity, 222Rn and 238U displayed statistically significant correlation (p < 0.05) with temperature and precipitation, suggesting a seasonal dependence. Therefore, the variability was attributed to mineral weathering, recharge through rocks and regolith with different NOR-content, and dilution by rapid recharge. The findings of this study show that activity concentrations of 222Rn in different types of water sources is affected by recharge patterns, which should be considered for when assessing drinking water quality.